2009
DOI: 10.1007/s11606-009-1180-9
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Quality of Medication Use in Older Adults: Baseline Findings from a Longitudinal Study

Abstract: Medication-related problems are prevalent in community-residing older adults. Blacks had more medication-related problems than whites, including higher rates of nonadherence. These findings require further study to better understand racial disparities in quality medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…However, many studies have shown self-report measures of adherence to be relatively accurate for predicting clinically meaningful outcomes (e.g., meta-analysis by Nieuwkerk & Oort, 2005) and their accuracy is improved by controlling for social desirability bias (Simoni et al, 2002), as we did in the present study. Although the reliability of the adherence measure was low (a = 0.58 at baseline and a = 0.60 at follow-up), we considered the measure acceptable because it has: (1) performed similarly in other studies (Jerant et al, 2008); (2) been widely used for a variety of medical conditions (Murray et al, 2007;Parienti et al, 2004;Roth et al, 2009); and (3) been shown to have predictive validity (Morisky et al, 1986) and concordance with pharmacy refill data (Krousel-Wood et al, 2009). Moreover, we obtained significant results despite the ''random noise'' of unreliability, which mitigates against a measure yielding results.…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies have shown self-report measures of adherence to be relatively accurate for predicting clinically meaningful outcomes (e.g., meta-analysis by Nieuwkerk & Oort, 2005) and their accuracy is improved by controlling for social desirability bias (Simoni et al, 2002), as we did in the present study. Although the reliability of the adherence measure was low (a = 0.58 at baseline and a = 0.60 at follow-up), we considered the measure acceptable because it has: (1) performed similarly in other studies (Jerant et al, 2008); (2) been widely used for a variety of medical conditions (Murray et al, 2007;Parienti et al, 2004;Roth et al, 2009); and (3) been shown to have predictive validity (Morisky et al, 1986) and concordance with pharmacy refill data (Krousel-Wood et al, 2009). Moreover, we obtained significant results despite the ''random noise'' of unreliability, which mitigates against a measure yielding results.…”
Section: Resultsmentioning
confidence: 99%
“…Race-related differences in cost-related underuse have been observed in outpatient studies, [6][7][8]12 and may be an important contributor to racial disparities in evidence-based medication use. [13][14][15] These differences may, in part, reflect racial variations in socioeconomic status; lower income patients, who are more likely to be from a racial or ethnic minority, are more sensitive to cost sharing than higher income individuals. 16 Consistent with this, the relationship between race and cost-related underuse in our study was smaller but still highly significant in multivariable models that adjusted for income.…”
Section: Discussionmentioning
confidence: 99%
“…While understandably this may be due to clinical need, black seniors are less likely to have a written list (record) of their medications and more likely to have medication-related problems, such as suboptimal monitoring. 145 They are also less likely to have adequate health literacy. 145,146 Further, elderly minorities who were not aware of Part D benefits were found to be less adherent to their antihypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…145 They are also less likely to have adequate health literacy. 145,146 Further, elderly minorities who were not aware of Part D benefits were found to be less adherent to their antihypertensive medications. 147 Medicare Part D Medication Therapy Management (MTM) programs 148 provide an excellent mechanism to address these drivers of poor adherence among minority seniors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation